Oxidative desaturation of α-linolenic, linoleic, and stearic acids by human liver microsomes - Tacconi de Gómez Dumm, Irma Nelva (1975)
The desaturation of stearic, linoleic, and α-linolenic acids by human liver microsomes were studied. The microsomes were isolated from liver biopsies obtained during operations. It was shown that human liver microsomes are able to desaturate 1-¹⁴C-α-linolenic acid to octadeca-6,9,12,15-tetraenoic acid; 1-¹⁴C-linoleic acid to γ-linolenic acid; and 1-¹⁴C-stearic acid to oleic acid in the same system described in the rat. However, the desaturation activity obtained was low compared to other mammals. This effect was attributed to fasting, premedication, or the anaesthesia.